Continuous Electronic Fetal Monitoring during Labor: A Critique and a Reply to Contemporary Proponents - Sartwelle, Thomas P.; Johnston, James C. (The Surgery Journal, 2018)
A half century after continuous electronic fetal monitoring (EFM) became the omnipresent standard of care for the vast majority of labors in the developed countries, and the cornerstone for cerebral palsy litigation, EFM advocates still do not have any scientific evidence justifying EFM use in most labors or courtrooms. Yet, these EFM proponents continue rationalizing the procedure with a rhetorical fog of meaningless words, misleading statistics, archaic concepts, and a complete disregard for medical ethics. This article illustrates the current state of affairs by providing an evidence-based review penetrating the rhetorical fog of a prototypical EFM advocate.
Keywords: electronic fetal monitoring; cerebral palsy; medical ethics; journal of child neurology; Dr. Max Wiznitzer; Dr. Marc Patterson